SOCIO-LEGAL CRITERIA FOR THE CLASSIFICATION OF CIVIL SOCIETY INSTITUTIONS (World Bulletin of Management and Law, 2026)
This article provides a comprehensive theoretical and legal analysis of the various socio-legal criteria used to classify civil society institutions. The study explores the multi-dimensional nature of these institutions, categorizing them based on functional domains, legal status, social interests, and their relational dynamics with state authorities. By examining both formal and informal structures, the author highlights how these classifications contribute to a better understanding of the legal framework and the social significance of non-governmental organizations in modern legal systems. The systematic approach used in this research allows for a clearer identification of the role each institute plays in protecting public interests and maintaining social stability.